The effect of polyethylene glycol upon DNA uptake in Neurospora crassa - M. Schablik; Zs. Feher; A. Zsindeley; G. Szabo (Fungal Genetics Reports, 1979)
The effect of polyethylene glycol upon DNA uptake in Neurospora crassa